(Re)structuring copyright : a comprehensive path to international copyright reform - Gervais, Daniel J., 1963- (Elgar monographs in intellectual property law, 2017)
As the Internet continues to alter our online world, the structure of copyright in its current form becomes inadequate and unfit for purpose. In this bold and persuasive work, Daniel Gervais argues that the international copyright system is in need of a root and branch rethink. This ambitious and far-reaching book sets out to diagnose in some detail the problems faced by copyright, before eloquently mapping out a path for comprehensive and structured reform. This book's main objectives are to identify structural and other deficiencies within the current system, and to outline a structured approach to copyright reform. Part I of the book is thus diagnostic in nature, Part II offers detailed and concrete pathways to improve the current system, whilst in the Epilogue, a clear path to revise the Berne Convention is proposed. Contributing a reasoned and novel voice to a debate that is all too often driven by ignorance and partisan self-interest, this book will be required reading for all copyright scholars and practitioners with an interest in the future direction of the field.